Intercultural communication in the Malaysian vision schools: implications for the management and leadership in a multicultural primary school - Othman, Azam; Ruslan, Norbaiduri; Sheikh Ahmad, Ismail (SAGE, 2012)
This article discusses intercultural communication in Vision Schools in Malaysia. It also elaborates the extent to which the Vision Schools foster racial interaction across the three major ethnic groups: Malays, Chinese, and Indians. A total of 887 primary school students were surveyed across the Vision Schools. It was found that the intercultural communication in the Vision Schools had triggered intercultural understanding and awareness of cultural diversity in the schools. The dynamics of intercultural interaction were, however, more profound in the national school compared to the other two vernacular schools (Chinese and Tamil national-type schools). Nevertheless, students seemed to appreciate national integration beyond their school experience. Despite their youth, the children understood the significance of maintaining and sustaining national unity. Inspiring school leadership towards fulfilling intercultural awareness and exposure will lead the establishment and existence of Vision Schools in the right direction.